The Lisbon process - a compromise between ambitions and reality - Peter Becker; Ognian N. Hishow (Stiftung Wissenschaft und Politik (SWP), 2005)
In Lisbon back in March 2000, the EU heads of state and government undertook to pursue the strategic objective of turning the Union into 'the most competitive and dynamic knowledge-based economy in the world' by 2010. The imminent mid-term review of the Lisbon Process constitutes an opportunity to inject fresh momentum into that strategy by focussing on its growth objectives, specifying the associated measures more precisely and developing a systemic approach that weighs Europe's ambitions against the reality of the situations in its Member States. (SWP Comments / SWP)
Keywords: 320